Time-lapse videos effects on students biology concept understanding and visual literacy skills - Angeles, Marvin John P. (College of Education, University of the Philippines Diliman, 2019)
This study examined the effects of Time-lapse Videos on students biology concept understanding and visual literacy skills. It hypothesized that the students visual literacy skills positively predict the students biology concept understanding . A pretest-posttest quasi-experimental design was employed in the study. It involved a total of 71 students comprising the Time-lapse Videos (TLV) and Conventional Instructional Materials (CIM) groups. The intervention lasted for five weeks during the last portion of the third quarter and the entire fourth quarter of Academic Year 2018-2019. The researchers used two research instruments: Biology Concept Understanding Test (BCUT) and Visual Literacy Skills Test (VLST). The BCUT was developed by the researcher while the VLST was adapted from the scale made by Arslan and Kipper. To analyze the data, t-test for independent samples, t-test for paired samples, and linear regression were conducted. The level of significance was set at 0.05 in all tests. Results revealed that there was significant difference in both students biology concept understanding and visual literacy skills between the TLV group and the CIM group. However, contrary to what was hypothesized, visual literacy skills do not positively predict concept understanding in Biology. The use of the Time-lapse Videos was recommended based on on the following : (1) its applicability to the lesson, (2) balanced and fair school guidelines on device usage, (3) professional development of in-service teachers, (4) the need for further research and training of curriculum developers and educational researchers regarding its used.